OPTIMISME PEDAGANG KAKI LIMA DALAM BERJUALAN DI KELURAHAN TUAH KARYA KECAMATAN TAMPAN KOTA PEKANBARU - Novita, Fitriana; Natuna, Daeng Ayub; Wilson, Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aims to determine the Accountability of Citizens Learning Package A B C while studying at PKBM Pelita Riau. The formulation of the problem in this study is how high is the accountability of citizens learning the A B C package in the learning process in Pelita Riau PKBM?. Optimistic street vendors selling street sidewalks where they have confidence that if they do not sell here they cannot fulfill their needs. The formulation of the problem in this study is how high is the optimism of street vendors in selling at Kelurahan TuahKarya Kecamatan Tampan?.The purpose of this study is to determine the level of optimism of street vendors in selling at Kelurahan Tuah Karya Kecamatan Tampan. This study has 4 indicators, namely (1) positive thinking, (2) realistic thinking, (3) beliefs,and (4) expectations. The population in this study were 75 street vendors. This research sample uses simple random sampling technique (simple random sampling). This technique is used because of the way the sampling is done without regard to strata in the population (Sugiyono, 2015: 93).Data collection techniques in this study were questionnaire techniques, which amounted to 40 statements. Data obtained from respondents totaling 20 people for the trial sample and 43 people for the study sample. After the questionnaire is tested, there are 2 invalid statements, and the researcher discards invalid statements. Based on the results of interpretation analysis obtained for each indicator of optimism in street vendors selling in Kelurahan Tuah Karya Kecamatan Tampan Kota Pekanbaruall classified as high, but this is all not optimal. So, the most dominant of these 4 indicators is realistic thinking. This means that the optimism of street vendors in selling on Kelurahan Tuah Karya Kecamatan Tampan Kota Pekanbaruseenfrom the way they can think realistically when facing problems in merchandise.Key Words: Optimism, Optimism of Street Vendors